2022
DOI: 10.3389/fimmu.2022.868973
|View full text |Cite
|
Sign up to set email alerts
|

Serum Immunoglobulins, Pneumonia Risk, and Lung Function in Middle-Aged and Older Individuals: A Population-Based Cohort Study

Abstract: IntroductionImmunoglobulins (Igs) play a pivotal role in host defense and prevention of pneumonia. Aging influences serum Ig levels, but the association between Igs and pneumonia in community-dwelling older individuals remains unknown. We evaluated the association of serum IgA, IgG, and IgM with pneumonia and lung function in middle-aged and older individuals.MethodsWe performed Cox and negative binomial regression analyses for the association of Igs with incident pneumonia and pneumonia-related mortality, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“… 7 , 8 In addition, there is some evidence suggestive of unfavourable properties associated with high serum IgG concentration among older individuals. 9 Our lifelong follow-up study on the health of a young and working age birth cohort population and their serum IgG concentrations suggests novel insights into the significance of adaptive immunity. 10 , 11 Highly intriguingly, not only the low IgG but also high serum IgG concentration in our cohort are associated with unfavourable outcomes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“… 7 , 8 In addition, there is some evidence suggestive of unfavourable properties associated with high serum IgG concentration among older individuals. 9 Our lifelong follow-up study on the health of a young and working age birth cohort population and their serum IgG concentrations suggests novel insights into the significance of adaptive immunity. 10 , 11 Highly intriguingly, not only the low IgG but also high serum IgG concentration in our cohort are associated with unfavourable outcomes.…”
Section: Discussionmentioning
confidence: 93%
“… 7 , 8 Among older individuals, even high serum IgG has been associated with risk of pneumonia-related mortality and recurrent pneumonia. 9 At an unselected population level, however, the significance of serum IgG concentrations on respiratory infection burden among the young and working age population is incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Reactions that occur due to decreased serum IgA levels can cause a decrease in the body's immunity which has an impact on respiratory tract disorders to exacerbate the degree of infection from pneumonia. 42 The limitation of the results of this study is that the sample size of children with LBW is too small so that it cannot represent the severity of pneumonia in West Java.…”
Section: Discussionmentioning
confidence: 94%
“…Diverging data regarding the serum immunoglobulin levels of pneumonia patients were published. Studies showed either lower ( 38 40 ) or higher ( 41 , 42 ) levels of IgA, nevertheless both were associated with an increased mortality risk. Data on alterations in mucosal antibody levels are scarce.…”
Section: Iga In Inflammatory Lung Diseasesmentioning
confidence: 99%